CONDENSER AND DEAERATOR CONTROL USING FUZZY-NEURAL TECHNIQUE - Ali, Prof. Dr. Abduladhem A.; Mohammed, A'ayad Sh. (Iraqi Journal for Electrical and Electronic Engineering, 2007)
A model reference adaptive control of condenser and deaerator of steam power plant is presented. A fuzzy-neural identification is constructed as an integral part of the fuzzy-neural controller. Both forward and inverse identification is presented. In the controller implementation, the indirect controller with propagating the error through the fuzzy-neural identifier based on Back Propagating Through Time (BPTT) learning algorithm as well as inverse control structure are proposed. Simulation results are achieved using Multi Input-Multi output (MIMO) type of fuzzy-neural network. Robustness of the plant is detected by including several tests and observations.